BK Channels Are Activated by Functional Coupling With L-Type Ca2+ Channels in Cricket Myocytes - Numata, Tomohiro; Sato-Numata, Kaori; Yoshino, Masami (Frontiers in Insect Science, 2021)
Large-conductance calcium (Ca2+)-activated potassium (K+) (BK) channel activation is important for feedback control of Ca2+ influx and cell excitability during spontaneous muscle contraction. To characterize endogenously expressed BK channels and evaluate the functional relevance of Ca2+ sources leading to BK activity, patch-clamp electrophysiology was performed on cricket oviduct myocytes to obtain single-channel recordings. The single-channel conductance of BK channels was 120 pS, with increased activity resulting from membrane depolarization or increased intracellular Ca2+ concentration. Extracellular application of tetraethylammonium (TEA) and iberiotoxin (IbTX) suppressed single-channel current amplitude. These results indicate that BK channels are endogenously expressed in cricket oviduct myocytes. Ca2+ release from internal Ca2+ stores and Ca2+ influx via the plasma membrane, which affect BK activity, were investigated. Extracellular Ca2+ removal nullified BK activity. Administration of ryanodine and caffeine reduced BK activity. Administration of L-type Ca2+ channel activity regulators (Bay K 8644 and nifedipine) increased and decreased BK activity, respectively. Finally, the proximity between the L-type Ca2+ channel and BK was investigated. Administration of Bay K 8644 to the microscopic area within the pipette increased BK activity. However, this increase was not observed at a sustained depolarizing potential. These results show that BK channels are endogenously expressed in cricket oviduct myocytes and that BK activity is regulated by L-type Ca2+ channel activity and Ca2+ release from Ca2+ stores. Together, these results show that functional coupling between L-type Ca2+ and BK channels may underlie the molecular basis of spontaneous rhythmic contraction.